Why fly the extra mile? Latitudinal trend in migratory fuel deposition rate as driver of trans-equatorial long-distance migration. - Y Aharon-Rotman; K Gosbell; C Minton; Marcel Klaassen (2016)
Trans-equatorial long-distance migrations of high-latitude breeding animals have been attributed to narrow ecological niche widths. We suggest an alternative hypothesis postulating that trans-equatorial migrations result from a possible increase in the rate at which body stores to fuel migration are deposited with absolute latitude; that is, longer, migrations away from the breeding grounds surpassing the equator may actually enhance fueling rates on the nonbreeding grounds and therewith the chance of a successful, speedy and timely migration back to the breeding grounds. To this end, we first sought to confirm the existence of a latitudinal trend in fuel deposition rate in a global data set of free-living migratory shorebirds and investigated the potential factors causing this trend. We next tested two predictions on how this trend is expected to impact the migratory itineraries on northward migration under the time-minimization hypothesis, using 56 tracks of high-latitude breeding shorebirds migrating along the East Asian-Australasian Flyway. We found a strong positive effect of latitude on fuel deposition rate, which most likely relates to latitudinal variations in primary productivity and available daily foraging time. We next confirmed the resulting predictions that (1) when flying from a stopover site toward the equator, migrants use long jumps that will take them to an equivalent or higher latitude at the opposite hemisphere; and (2) that from here onward, migrants will use small steps, basically fueling only enough to make it to the next suitable staging site. These findings may explain why migrants migrate "the extra mile" across the equator during the nonbreeding season in search of better fueling conditions, ultimately providing secure and fast return migrations to the breeding grounds in the opposite hemisphere.